2020
DOI: 10.1093/jisesa/ieaa107
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles and Binding Properties of the Chemosensory Protein PxylCSP11 from the Diamondback Moth, Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: The diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae) is one of the most destructive pests to cruciferous plants worldwide. The oligophagous moth primarily utilizes its host volatiles for foraging and oviposition. Chemosensory proteins (CSPs) are soluble carrier proteins with low molecular weight, which recognize and transport various semiochemicals in insect chemoreception. At present, there is limited information on the recognition of host volatiles by CSPs of P. xylostella. Here, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Previous studies showed that OBP genes were highly expressed in insect heads, suggesting that they contribute to the detection of host plant volatiles and sex pheromones (Chang et al, 2015;Liu et al, 2015;Wang et al, 2016). The following studies also showed that the indicated CSPs are highly expressed in the male antennae of the following insects: CSP11 of Plutella xylostella (Fu et al, 2020), CSP8 of Nilaparvata lugens (Waris et al, 2018), CSP1 of Cylas formicarius (Hua et al, 2021), and CSP3 of Cnaphalocrocis medinalis (Zeng et al, 2018). High expression of CSP in male antennae suggests that they may be more involved in the perception of sex pheromones than plant volatiles.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed that OBP genes were highly expressed in insect heads, suggesting that they contribute to the detection of host plant volatiles and sex pheromones (Chang et al, 2015;Liu et al, 2015;Wang et al, 2016). The following studies also showed that the indicated CSPs are highly expressed in the male antennae of the following insects: CSP11 of Plutella xylostella (Fu et al, 2020), CSP8 of Nilaparvata lugens (Waris et al, 2018), CSP1 of Cylas formicarius (Hua et al, 2021), and CSP3 of Cnaphalocrocis medinalis (Zeng et al, 2018). High expression of CSP in male antennae suggests that they may be more involved in the perception of sex pheromones than plant volatiles.…”
Section: Discussionmentioning
confidence: 98%
“…The compound 2,4-dimethylheptane also elicited strong EAG and behavioural responses in P. xylostella. Fu et al (2020) found F I G U R E 2 Gas chromatography coupled with electroantennographic detection (GC-EAD) responses of female adults of Plutella xylostella to headspace volatiles from wounded Mentha spicata. The four components with electroantennographic detectionactivity were confirmed to be 2,4-dimethyl-heptane, 4-methyloctane, 2-methylnonane and myrcene by gas chromatography-mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…We next conducted the binding experiments with several candidate ligand molecules. These molecules have been demonstrated to bind to different CSP proteins in the literature [ 8 , 12 , 27 , 28 , 29 ]. Our results showed that the SlCSP8 protein has the highest and lowest affinities to rhodojaponin III and avermectin, respectively, while it displays moderate affinities to 12-bromododecanol and bombykol, with the former being a better binder than the latter.…”
Section: Discussionmentioning
confidence: 99%